Letter: is the AHHS score really useful in clinically severe alcoholic hepatitis?. Issue 10 (21st April 2021) - Buchard, Benjamin; Sévigné, Luc; Darcha, Claude; Muti, Leon; Joubert, Juliette; Abergel, Armand
Abstract : LINKED CONTENT This article is linked to Forrest et al paper. To view this article, visit https://doi.org/10.1111/apt.16157